Case report: Identification of facioscapulohumeral muscular dystrophy 1 in two siblings with normal phenotypic parents using optical genome mapping - Jiang, Jieni; Cai, Xiaotang; Qu, Haibo; Yao, Qiang; He, Tiantian; Yang, Mei; Zhou, Hui; Zhang, Xuemei (Frontiers in Neurology, 2024)
Objective Facioscapulohumeral muscular dystrophy type 1 (FSHD1) is one of the most common forms of autosomal-dominant muscular dystrophies characterized by variable disease penetrance due to shortened D4Z4 repeat units on 4q35. The molecular diagnosis of FSHD1 is usually made by Southern blotting, which is complex, time-consuming, and lacks clinical practicality. Therefore, in this study, optical genome mapping (OGM) is employed for the genetic diagnosis of FSHD1. Furthermore, epigenetic heterogeneity is determined from methylation analysis. Methods Genomic DNA samples from four members of the same family were subjected to whole-exome sequencing. OGM was used to identify structural variations in D4Z4, while sodium bisulfite sequencing helped identify the methylation levels of CpG sites in a region located distally to the D4Z4 array. A multidisciplinary team collected the clinical data, and comprehensive family analyses aided in the assessment of phenotypes and genotypes. Results Whole-exome sequencing did not reveal variants related to clinical phenotypes in the patients. OGM showed that the proband was a compound heterozygote for the 4qA allele with four and eight D4Z4 repeat units, whereas the affected younger brother had only one 4qA allele with four D4Z4 repeat units. Both the proband and her younger brother were found to display asymmetric weakness predominantly involving the facial, shoulder girdle, and upper arm muscles, whereas the younger brother had more severe clinical symptoms. The proband's father, who was found to be normal after a neurological examination, also carried the 4qA allele with eight D4Z4 repeat units. The unaffected mother exhibited 49 D4Z4 repeat units of the 4qA allele and a minor mosaic pattern with four D4Z4 repeat units of the 4qA allele. Consequently, the presence of the 4qA allele in the four D4Z4 repeat units strongly pointed to the occurrence of maternal germline mosaicism. The CpG6 methylation levels were lower in symptomatic patients compared to those in the asymptomatic parents. The older sister had lower clinical scores and ACSS and higher CpG6 methylation levels than that of her younger brother. Conclusions In this study, two siblings with FSHD1 with phenotypically normal parents were identified by OGM. Our findings suggest that the 4qA allele of four D4Z4 repeats was inherited through maternal germline mosaicism. The clinical phenotype heterogeneity is influenced by the CpG6 methylation levels. The results of this study greatly aid in the molecular diagnosis of FSHD1 and in also understanding the clinical phenotypic variability underlying the disease.